A Smart Hyperthermia Nanofiber with Switchable Drug Release for Inducing Cancer Apoptosis. (14th June 2013) - Kim, Young‐Jin; Ebara, Mitsuhiro; Aoyagi, Takao
Abstract A smart hyperthermia nanofiber is described with simultaneous heat generation and drug release in response to 'on‐off' switching of alternating magnetic field (AMF) for induction of skin cancer apoptosis. The nanofiber is composed of a chemically‐crosslinkable temperature‐responsive polymer with an anticancer drug (doxorubicin; DOX) and magnetic nanoparticles (MNPs), which serve as a trigger of drug release and a source of heat, respectively. By chemical crosslinking, the nanofiber mesh shows switchable changes in the swelling ratio in response to alternating 'on‐off' switches of AMF because the self‐generated heat from the incorporated MNPs induces the deswelling of polymer networks in the nanofiber. Correspondingly, the 'on‐off' release of DOX from the nanofibers is observed in response to AMF. The 70% of human melanoma cells died in only 5 min application of AMF in the presence of the MNPs and DOX incorporated nanofibers by double effects of heat and drug. Taken together these advantages on both the nano‐ and macroscopic scale of nanofibers demonstrate that the dynamically and reversibly tunable structures have the potential to be utilized as a manipulative hyperthermia material as well as a switchable drug release platform by simple switching an AMF 'on' and 'off'.